An Effect of Using Group Investigation Method to Improving Critical Thinking Skill - Yohana Puspita Dewi; Wiratno, Purna; Herlisya, Destia (STKIP PGRI Bandar Lampung, 2024)
Student’s critical thinking ability can be improved through a good learning process. For that, the learning process should be packaged in such a way that students are actively involved in the classroom. The effort to obtain these results is to improve the quality of learning through the use of good teaching materials. Learning to teach is a process that not only get information from lecturers but many activities and actions that should be done, in achieving better learning outcomes for students. For example from the provision of tasks that stimulate students to think critically, provided with methods and learning models in learning. The learning process is essentially a teaching-learning process that emphasizes the importance of learning through experience processes to gain experience. This research purpose is to identify the process and results of the implementation of group investigation learning model in improve of critical thinking skill. Students' critical thinking is needed, because during the learning process students develop ideas about the problems contained in learning. Some students difficult to think creatively when they learn in English. They difficult to share their ideas, they lack of vocabulary, and they diffiult to create an idea to solve the problem when their teacher ask them to discuss topic in English. Such as education problem, the effect of technology for students and etc.